2004
DOI: 10.1152/jn.00047.2004
|View full text |Cite
|
Sign up to set email alerts
|

Eyes on Target: What Neurons Must do for the Vestibuloocular Reflex During Linear Motion

Abstract: Angelaki, Dora E. Eyes on target: what neurons must do for the vestibuloocular reflex during linear motion. J Neurophysiol 92: 20 -35, 2004; 10.1152/jn.00047.2004. A gaze-stabilization reflex that has been conserved throughout evolution is the rotational vestibuloocular reflex (RVOR), which keeps images stable on the entire retina during head rotation. An ethological newer reflex, the translational or linear VOR (TVOR), provides fast foveal image stabilization during linear motion. Whereas the sensorimotor pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 173 publications
3
72
0
2
Order By: Relevance
“…Angelaki, 2004;Thurtell et al, 1999). Zhou and colleagues (2004Zhou and colleagues ( , 2005Zhou and colleagues ( , 2007 found that click-evoked eye movements and abducens activity in monkeys changed with different horizontal starting positions of the eye.…”
Section: Discussionmentioning
confidence: 99%
“…Angelaki, 2004;Thurtell et al, 1999). Zhou and colleagues (2004Zhou and colleagues ( , 2005Zhou and colleagues ( , 2007 found that click-evoked eye movements and abducens activity in monkeys changed with different horizontal starting positions of the eye.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Polysynaptic pathways also have a critical role in mediating the utriculo-ocular reflex. [8][9][10] Signals from the lateral utricle ipsilateral to the direction of head translation are transmitted to the ipsilateral vestibular nucleus, via an extensive network of projections within the cerebellum (including the nodulus, ventral uvula, fastigial nucleus, anterior vermis, and flocculus/ventral paraflocculus). Polysynaptic pathways are also responsible for generating ocular counterroll movements during static head tilt.…”
Section: Anatomy and Physiology Of The Otolithsmentioning
confidence: 99%
“…Polysynaptic pathways are also responsible for generating ocular counterroll movements during static head tilt. 10 …”
Section: Anatomy and Physiology Of The Otolithsmentioning
confidence: 99%
“…1,6 There is growing evidence, however, that this disynaptic pathway is weak and that polysynaptic pathways via the cerebellum play a more important role. 35 Lesions in the vestibular periphery, vestibular nuclei, medulla, and the caudal pons cause ipsilesional hypotropia and head tilt. Because otolithic projections from the vestibular nuclei cross the midline at the level of the pons to ascend along the medial longitudinal fasciculus, lesions in the rostral pons and midbrain cause contralesional hypotropia and head tilt (eg, internuclear ophthalmoplegia or midbrain lesions).…”
mentioning
confidence: 99%